2021
DOI: 10.1093/jnci/djab129
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Thromboxane B2 and Lethal Prostate Cancer in African American Men

Abstract: Background Thromboxane A2 (TXA2) is a platelet- and cyclooxygenase-derived eicosanoid that has been linked to metastasis. We investigated the role of TXA2 in the development of lethal prostate cancer in African American (AA) and European American (EA) men. Methods We measured urinary 11-dehydrothromboxane B2 (TXB2), a stable metabolite of TXA2, with mass-spectrometry. Samples were obtained from 977 cases and 1022 controls at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…However, Drew et al reported approximately 20-25% of participants in the ASPIRED study who were randomized to 81 or 325 mg/day of aspirin experienced no inhibition or even an increase in PGE-M from baseline despite demonstrating a strong inhibition of urinary thromboxane B2 [22]. This finding is consistent with our data, where in a previous study, using the same cohort of participants, we reported strong thromboxane B2 inhibition in aspirin users across both cases and controls [38]. This suggests that the participants in our study are not nonresponders to aspirin, but rather, aspirin use mechanistically is not targeting PGE-M in these men.…”
Section: Discussionsupporting
confidence: 92%
“…However, Drew et al reported approximately 20-25% of participants in the ASPIRED study who were randomized to 81 or 325 mg/day of aspirin experienced no inhibition or even an increase in PGE-M from baseline despite demonstrating a strong inhibition of urinary thromboxane B2 [22]. This finding is consistent with our data, where in a previous study, using the same cohort of participants, we reported strong thromboxane B2 inhibition in aspirin users across both cases and controls [38]. This suggests that the participants in our study are not nonresponders to aspirin, but rather, aspirin use mechanistically is not targeting PGE-M in these men.…”
Section: Discussionsupporting
confidence: 92%
“…TXB2 is a stable metabolite of thromboxane A2 (TXA2), which is derived from cyclooxygenase (COX) and PLTs. TXA2 has been linked to cardiovascular diseases, Type 1 and 2 diabetes, chronic inflammatory diseases, and tumour metastasis 22,23 . Consistent with our study, increased expression of enzymes in the COX pathway was discovered in muscles from DM/PM patients 24 .…”
Section: Discussionsupporting
confidence: 88%
“…TXA2 has been linked to cardiovascular diseases, Type 1 and 2 diabetes, chronic inflammatory diseases, and tumour metastasis. 22,23 Consistent with our study, increased expression of enzymes in the COX pathway was discovered in muscles from DM/PM patients. 24 These prostanoid signalling molecules play an important role in muscle inflammation and atrophy.…”
Section: Potential Metabolic Biomarkers In Iim Main Subtypessupporting
confidence: 89%
“…Noteworthy, arachidonic acid can be further metabolized by the cyclooxygenase and 5-lipoxygenase enzymes, resulting in the synthesis of pro-in ammatory eicosanoids. One eicosanoid, the pro-metastatic thromboxane A2, has recently been linked by our group to an increased risk of lethal prostate cancer among African American men 34 . Nonetheless, the FADS1/2 locus has not been previously linked to prostate cancer in most studies 32 .…”
Section: Discussionmentioning
confidence: 95%